2001
DOI: 10.1002/1521-4095(200111)13:22<1701::aid-adma1701>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Well-Aligned Boron Nanowire Arrays

Abstract: Vertically aligned boron nanowires in self‐assembled large‐scale arrays with excellent uniformity and high density have been fabricated using radio‐frequency magnetron sputtering of boron and B2O3 powder onto various substrates. The nanowires thus produced are several tens of micrometers long and 20–80 nm wide, with typically platform‐shaped tips (see Figure for a high‐magnification SEM image).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(55 citation statements)
references
References 1 publication
0
55
0
Order By: Relevance
“…15 Besides the metallic sheets and nanotubes there is a growing body of literature on semi-conducting boron nanostructures that are probably related to the known bulk crystal structures. [22][23][24][25][26] These developments indicate the rise of a very promising branch of nanoscience based on boron nanostructures. 26,27 Despite these early successes in the synthesis and characterization of BNTs, many questions on their structure and physical properties remain open and even their existence is still debated.…”
Section: Introductionmentioning
confidence: 99%
“…15 Besides the metallic sheets and nanotubes there is a growing body of literature on semi-conducting boron nanostructures that are probably related to the known bulk crystal structures. [22][23][24][25][26] These developments indicate the rise of a very promising branch of nanoscience based on boron nanostructures. 26,27 Despite these early successes in the synthesis and characterization of BNTs, many questions on their structure and physical properties remain open and even their existence is still debated.…”
Section: Introductionmentioning
confidence: 99%
“…In this section we describe the first growth of pure boron nanowires and their highly ordered arrays using a magnetron sputtering of high-purity B/B 2 O 3 and/or boron targets (Cao et al, 2001(Cao et al, , 2002a(Cao et al, , 2002b. In a typical experiment, a radio frequency (rf) magnetron sputtering of 80 W power was employed to prepare aligned boron nanowire arrays films.…”
Section: Fig 1 Schematic Of the Electronic Charge Distributions (Thmentioning
confidence: 99%
“…We found that the formation of boron nanowire arrays is independent from the nature of the substrate. We can obtain well-ordered boron nanowire films with high quality on a set of different substrates, such as SiO 2 wafer, Al 2 O 3 wafer, MgO wafer, and many other metal and non-metal plates (Cao et al, 2001(Cao et al, , 2002a(Cao et al, , 2002b. The boron nanowire is sheathed by an amorphous oxide coating that is formed when the boron nanowires are exposed to air after deposition.…”
Section: Fig 1 Schematic Of the Electronic Charge Distributions (Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Stimulated by these intriguing properties of bulk boron, researchers have made great effort in synthesizing one dimensional (1D) boron nanomaterials utilizing a variety of techniques, such as radio-frequency magnetron sputtering [6], chemical vapor deposition (CVD) [7,8], laser ablation technique [9][10][11], and carbothermal reactions [12,13]. Such 1D boron nanomaterials are expected to possess various bulk properties, and they may serve as nanobuilding blocks for the next generation sensors, electric devices, vacuum microelectronics, nano/microelectromechanical systems (NEMS/MEMS) and other high-temperature electronics.…”
Section: Introductionmentioning
confidence: 99%